Effects of Event Service Quality on the Quality of Life and Behavioral Intentions of Recreational Runners. (21st December 2021) - Ma, Shang-Chun; Kaplanidou, Kyriaki
ABSTRACT: This study examined how three components of sporting event service quality—physical environment, interaction, and outcome qualities—influence runners' regular exercise intention (REI), quality of life (QoL), and repeat participation intention (RPI). Data were collected from 573 runners in Taiwan and 228 runners in Greece. A multigroup analysis was used to compare the two countries. Results revealed that the quality of both events' physical environment indirectly influenced RPI through QoL benefits. Further, in the Taiwan sample, outcome quality indirectly influenced RPI through REI and QoL benefits. There were significant differences between the Taiwan and Greece samples in the relationships among outcome quality, QoL benefits, REI, and RPI. This study explored how sporting event service quality affects economic and social outcomes by drawing on multiple theoretical bases and adopting a cross-national perspective.